Avaliação do ácido hialurônico de alto peso molecular como tratamento da sinovite experimental em equinos - Ribeiro, Marcela dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Synovitis frequently affects athletes, whether they are equines or humans. The occurrence of injuries within the articular environment, whether mechanical or pathogen-induced, disrupts articular homeostasis, leading to the release of inflammatory factors into the synovial fluid. The established inflammatory process contributes to chondral degradation due to the release of interleukins and matrix metalloproteinases, predisposing the joint to osteoarthritis. The objective of this study was to evaluate the influence of hyaluronic acid treatment on acute experimental synovitis in equines compared to untreated animals. Synovitis was induced in adult equines (n=16) in the radiocarpal joint, without prior articular alteration, using LPS (0.25 ng). Twelve hours after induction, the animals received the treatment: the treated group received high molecular weight hyaluronic acid (20 mg/ml, 2.280 kDa), while the control group received PBS (2 ml). The animals were rigorously evaluated at 0 (immediately before synovitis induction), 12, 24, and 48 hours post-induction, and at 7 and 14 days post-induction through orthopedic examination, ultrasonography, and thermography of the joint and synovial fluid. The evaluation results were subjected to the Shapiro-Wilk normality test. Parametric data were analyzed using ANOVA followed by Tukey's test, while non-parametric data were analyzed using the Mann-Whitney test, with comparisons made using Friedman's test. Statistical significance was considered when p<0.05. Supplementation with hyaluronic acid was effective in providing analgesia in treated animals and remained stable in the joint for at least 36 hours after application, maintaining the presence of high molecular weight molecules within the articular environment.

A sinovite acomete frequentemente atletas, sejam equinos ou até mesmo o homem. O surgimento de lesões no ambiente articular, seja mecânico ou por patógenos, alteram a homeostase articular, havendo a liberação de fatores inflamatórios no líquido sinovial. O processo inflamatório estabelecido, corrobora para a degradação condral, devido a liberação de interleucinas e metaloproteinases de matriz, sendo um fator predisponente para a osteoartrite. O objetivo deste trabalho foi avaliar a influência do tratamento com ácido hialurônico de alto peso molecular sobre a sinovite experimental aguda em equinos comparado a animais não tratados. A sinovite foi induzida com LPS(0,25ng) em equinos adultos (n = 16) na articulação rádio cárpica, sem alteração articular e após 12 horas da indução, receberam o tratamento, sendo o grupo tratado com ácido hialurônico (20 mg/ml) de alto peso molecular (2.280 KDa) e o grupo controle PBS (2 ml). Os animais foram avaliados rigorosamente nos momentos 0 (imediatamente antes da indução da sinovite), 12, 24 e 48 horas após a indução e 7 e 14 dias após a indução da sinovite, através de exame ortopédico, do líquido sinovial, ultrassonografia e termografia da articulação. Os resultados das avaliações foram submetidos a teste de normalidade (Shapiro wilk) e aqueles que apresentaram comportamento paramétrico passaram pela ANOVA, seguido pelo teste de Tukey. As análises não paramétricas passaram pelo teste de Mann-Whitney, sendo as comparações realizadas pelo teste de Friedman. A diferença estatística foi considerada quando p<0,05. A suplementação com o ácido hialurônico foi eficaz em reduzir a claudicação nos animais tratados, tendo ainda se mantido estável na articulação por pelo menos 36 horas após sua aplicação, mantendo a presença de moléculas de alto peso molecular no ambiente articular. Palavras-chave: peso molecular, inflamação, líquido sinovial, articulação.
Evaluation of high molecular weight hyaluronic acid as a treatment for experimental synovitis in equines.
Keywords: Peso molecular; Inflamação; Liquido sinovial; Articulação